Feeling Appreciated Buffers Against the Negative Effects of Unequal Division of Household Labor on Relationship Satisfaction. (August 2022) - Gordon, Amie M.; Cross, Emily; Ascigil, Esra; Balzarini, Rhonda; Luerssen, Anna; Muise, Amy
Decades of research from across the globe highlight unequal and unfair division of household labor as a key factor that leads to relationship distress and demise. But does it have to? Testing a priori predictions across three samples of individuals cohabiting with a romantic partner during the COVID-19 pandemic ( N = 2, 193, including 476 couples), we found an important exception to this rule. People who reported doing more of the household labor and who perceived the division as more unfair were less satisfied across the early weeks and ensuing months of the pandemic, but these negative effects disappeared when people felt appreciated by their partners. Feeling appreciated also appeared to buffer against the negative effects of doing less, suggesting that feeling appreciated may offset the relational costs of unequal division of labor, regardless of who contributes more. These findings generalized across gender, employment status, age, socioeconomic status, and relationship length.